2018
DOI: 10.3390/nu10030310
|View full text |Cite
|
Sign up to set email alerts
|

Generic Meal Patterns Identified by Latent Class Analysis: Insights from NANS (National Adult Nutrition Survey)

Abstract: Nutritional data reduction methods are widely applied in nutrition epidemiology in order to classify individuals into meaningful groups with similar dietary patterns. To date, none of the existing studies have applied latent class analysis to examine dietary patterns which include meal types consumed throughout a day. We investigated main meal patterns followed on weekend and weekdays, and evaluated their associations with cardio-metabolic biomarkers. The analyses were performed within the NANS (National Adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…As for the applicable conditions, model parameters or implementation steps of the LCA, this paper will not be redundant. Studies in this field can be observed in previous studies [31,32,33,34].…”
Section: Methodsmentioning
confidence: 91%
“…As for the applicable conditions, model parameters or implementation steps of the LCA, this paper will not be redundant. Studies in this field can be observed in previous studies [31,32,33,34].…”
Section: Methodsmentioning
confidence: 91%
“…To assess how breakfast regularity related to the type of meal consumed during the remainder of the day, we used a generic meal coding system, previously applied to the NANS dataset. The methodology has been described in detail elsewhere [ 15 , 16 ]. The available dietary data on food items was reduced to 20 pre-defined food categories, with meal types corresponding to each of those categories.…”
Section: Methodsmentioning
confidence: 99%
“…Within each meal type, the combination of all food groups consumed by one person on a single survey day was identified as an individual meal. The individual meals were grouped into generic categories, including 6 generic light meal categories (skipped light meal, meat/fish/dairy sandwich, dairy sandwich, meat or fish sandwich, soups or salads, rice/potato/past and, other) and 4 generic main meals (skipped main meal, protein- and carbohydrate-based, protein-based, and carbohydrate-based main meals) [ 16 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, little is known about the combinations of foods consumed simultaneously during specific eating occasions [14][15][16][17][18][19][20][21][22][23], mainly because of a lack of practical assessment tools. There exist a near-infinite number of feasible food combinations, resulting in an unmanageable number of individual meals.…”
Section: Introductionmentioning
confidence: 99%